An exploratory study of psychological and decision-making outcomes among family members of critically ill patients - Marym M. Alaamri; Shoroug Shaker Darweesh; Sarah Wasl Algabasani; Sarah Mohammad Alsubiei; Nora Jaber Alsolami; Hanan Mohsen Alhaddad; Afnan Tunsi; Aisha Alhofaian (PLoS ONE, 2025)
Introduction Family members of critically ill patients are often required to make complex medical decisions under emotional distress, which may affect their decision-making capacity. It is well known that psychological distress can interfere with cognitive processes that are essential for decision-making; indeed, depression and anxiety constitute some examples of such distress. Aim This exploratory study examined psychological outcomes among family members of critically ill patients, specifically depression, anxiety, and stress. It also explored the relationships between these outcomes and decision-making self-efficacy. Methods The study included 90 family members of intensive care unit patients. Demographic data was collected, and participants completed the Depression, Anxiety, and Stress Scale (DASS-21) and a measure of decision-making self-efficacy. Correlation analysis was used to analyze the data. Findings The results showed participants suffering from varying levels of psychological distress, ranging from moderate to very high levels. To be specific, 61.1% of the respondents reported experiencing moderate to severe depression; furthermore, 67.2% of them suffered from moderate to severe levels of anxiety while 58.3% experienced moderate to severe stress. Statistical analysis revealed there was a significant inverse correlation between levels of distress and decision-making self-efficacy (r = −0.42, p < 0.001). Conclusion Psychological distress may affect the confidence of family members in medical decision-making. The findings emphasize the need for psychological support, with structured opportunities to aid in the decision-making capacity in critical care settings.